Hiding Secrets in Software: A Cryptographic Approach to Program Obfuscation. - Garg, Sanjam; Gentry, Craig; Halevi, Shai; Raykova, Mariana; Sahai, Amit; Waters, Brent (Communications of the ACM, 2016)
Can we hide secrets in software? Can we obfuscate programs-- that is, make programs unintelligible while preserving their functionality? What exactly do we mean by "unintelligible"? Why would we even want to do this? In this article, we describe some rigorous cryptographic answers to these quasi-philosophical questions. We also discuss our recent "candidate indistinguishability obfuscation" scheme and its implications.